Study of strength and ductility of high strength concrete columns - Tan, Eyin Yee Yin (2014)
The objective of this report is to study the strength and ductility of high strength concrete columns by the use of analysis software. Research was done by Li Bing and R. Park in 2004, deriving upon equations which can be used for quantities of confining reinforcement required in high strength concrete columns for adequate ductility.